Psychometric properties of the Social Anomia Scale in Peruvian drug-dependent patients - Aaron Caycho (Interacciones)
This study analyzes the structure and internal consistency of the Social Anomia Scale in drug-dependent patients. A total of 232 male drug addicts between 18 and 60 years of age, belonging to four therapeutic communities of Lima, were evaluated. The results obtained indicate low fit indices for the original Yañez model (2011); however, the proposed Model 2 replicates a structure of 17 items distributed in three underlying factors. Likewise, the discriminant validity and the Omega coefficient were obtained for the three factors found, as well as the measurement of factor invariance between groups of young adults and adults. The findings indicate that the structure and internal consistency of the Social Anomia Scale in the proposed model shows psychometric characteristics suitable for use in clinical contexts and social studies.